2011
DOI: 10.1016/j.ejcts.2010.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a low ejection fraction on long-term survival in systematic off-pump coronary artery bypass surgery

Abstract: Off-pump coronary artery bypass surgery can be performed adequately and safely in poor EF patients. However, overall and cardiac survival was decreased in this subset of patients with a comparable freedom from major cardiac adverse related events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
5
1
Order By: Relevance
“…Carmelo et al declared that female gender was associated with the need for surgery that is similar to the results of this study (P=0.000) (15). Simon Maltais et al demonstrated that the average age was not significant that it is in line with the findings of the present study (P=0.454) (16). Kazim et al reported in patients with EF below 30% the use of IABP is significant (P= 0.000); however, there was no difference between the number of patients' graft with EF below 30% and EF above 30% (P= 0.957) that are comparable with this study (P=0.863).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Carmelo et al declared that female gender was associated with the need for surgery that is similar to the results of this study (P=0.000) (15). Simon Maltais et al demonstrated that the average age was not significant that it is in line with the findings of the present study (P=0.454) (16). Kazim et al reported in patients with EF below 30% the use of IABP is significant (P= 0.000); however, there was no difference between the number of patients' graft with EF below 30% and EF above 30% (P= 0.957) that are comparable with this study (P=0.863).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, renal failure in patients was 2.5%, which was less than that in a study by Maltais S et al (16). Moreover, according to our results addiction was related with mortality after CABG surgery (0.002).…”
Section: Discussioncontrasting
confidence: 59%
“…Reduced LVEF is an established risk factor for perioperative complications and mortality after CABG [ 8 , 25 ]. Although recent studies indicate that off-pump CABG may be associated with benefits compared to on-pump CABG in reduced LVEF patients [ 26 , 27 ], all-cause and cardiovascular mortality was increased in this subset of patients [ 27 ]. In our cohort, LVEF ≤ 45% increased the risk of long-term mortality three-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular surgeons have encountered more patients with left ventricle dysfunction recently because of increased number of coronary artery interventions [3]. It was of increased interest for surgical treatment of ischemic cardiomyopathy because of limited donor candidates for transplantation.…”
Section: Discussionmentioning
confidence: 99%